Mechanical recycling of printed flexible plastic packaging: The role of binders and pigments - Lisiecki, M.; Belé, Tiago; Ügdüler, S.; Fiorio, R.; Astrup, T. F.; De Meester, S.; Ragaert, K. (Journal of Hazardous Materials, 2024)
Low-density polyethylene (LDPE), extensively employed in flexible plastic packaging, often undergoes printing with inks. However, during the mechanical recycling of post-consumer waste, these inks act as contaminants, subsequently compromising the quality and usability of recycled material. To understand better exactly which ink components cause which effects, this study comprehensively assesses the thermal behavior of three organic pigments and two commonly utilised binders, correlated with the impact on the mechanical recycling of LDPE-based flexible plastic packaging. In this regard, the study focuses on four pivotal factors: processability, mechanical properties, aesthetic attributes, and volatile organic compound profiles. The results indicate that nitrocellulose, used as a binder, degrades during reprocessing, resulting in film discoloration and the emission of potentially odorous compounds. Conversely, pigments are found to be dispersed within droplets of polyurethane binder in LDPE recyclates, whilst reprocessing printed samples detrimentally affects film properties, notably dart drop impact resistance, strain at break, and the number of inclusions. Additionally, it is shown that both inks comprise components that emit volatile compounds during reprocessing: non-thermally stable components, nitrocellulose and pigment yellow PY13, as well as low-molecular weight molecules from polyurethane and by-products from wax, plasticisers, and additives.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Design for circularity; Mechanical recycling; Solvent-based ink